2020
DOI: 10.1590/1516-3180.2020.0010.r1.28032020
|View full text |Cite
|
Sign up to set email alerts
|

Use of smartphone-based instant messaging services in medical practice: a cross-sectional study

Abstract: Use of telemedicine has become more frequent and more convenient for addressing medical issues. 1 It is perfectly suited for use in the modern world because of its cost-efficiency, its availability in remote and rural areas, the improved access to care that it provides and its shorter response time. It can also improve the consistency and quality of healthcare. 2 In 2018, data from the International Telecommunications Union showed that there were more than 3.9 billion active mobile phone (cellphone) subscripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In this context, several previous descriptive studies have noted the negative impacts of smartphones in healthcare facilities. 22 , 23 , 24 , 25 , 26 , 27 One such study suggested that ethical and legal regulations in the use of these smartphones in healthcare facilities should be developed to limit their abuse, 40 as they found that 40% of healthcare employees were uneducated about their workplace policy, which could potentially cause distraction or privacy breach of confidential healthcare data. Furthermore, other studies have found that only 31% of healthcare institutions have a social media policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, several previous descriptive studies have noted the negative impacts of smartphones in healthcare facilities. 22 , 23 , 24 , 25 , 26 , 27 One such study suggested that ethical and legal regulations in the use of these smartphones in healthcare facilities should be developed to limit their abuse, 40 as they found that 40% of healthcare employees were uneducated about their workplace policy, which could potentially cause distraction or privacy breach of confidential healthcare data. Furthermore, other studies have found that only 31% of healthcare institutions have a social media policy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other studies have found that only 31% of healthcare institutions have a social media policy. 40 , 41 This is worrying because executing policies regarding personal smartphone use during work hours is vital in protecting confidential medical information and preventing distractions. The findings regarding this factor analysis also agree with those of other studies, which revealed that smartphones at healthcare facilities risked distraction and microbial transmission, as their microbial load has been documented in various researches.…”
Section: Discussionmentioning
confidence: 99%
“…Both its technical conditions and its rapid incorporation into almost any area of life today [8] have made it the perfect nexus. In fact, nowadays it is not surprising that applications such as Instagram [9], or others more associated with instant messaging [10], are among the most frequented practices when accessing these mobile devices [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are numerous challenges to its execution. For example, the Federal Medical Council of Brazil has regarded the practice of telemedicine (between patient and doctor) as not lawful [ 19 ]. Likewise, in most states in the USA, the utilization of telemedicine is extremely compelled by administrative bodies.…”
mentioning
confidence: 99%